Quadratus lumborum block provides significant pain relief after abdominal transplant - Christopher Adam Godlewski (Wolters Kluwer Medknow Publications, 2020)
Abdominal organ transplantation - and more specifically small bowel transplant - can be quite painful, generally requiring significant opioid administration with the attendant negative ramifications. We present contrasting experiences with a gentleman who underwent transplantation for Crohn's disease and his retransplantation with the addition of post-operative anterior Quadratus Lumborum (QL) block. After the index procedure, he had significant pain and discomfort. The addition of the QL block lead to substantial improvement in both subjective and objective endpoints. While each case is different, a QL block can be a useful adjunct to achieve pain control, decrease opioid requirements, and potentially facilitate early extubation.